2017
DOI: 10.1371/journal.pone.0183689
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear envelope-distributed CD147 interacts with and inhibits the transcriptional function of RING1 and promotes melanoma cell motility

Abstract: Melanoma accounts for nearly 80% of all deaths associated with skin cancer.CD147 plays a very important role in melanoma progression and the expression level may correlate with tumor malignancy. RING1 can bind DNA and act as a transcriptional repressor, play an important role in the aggressive phenotype in melanoma. The interactions between CD147 and RING1 were identified with a yeast two-hybrid and RING1 interacted with CD147 through the transmembrane domain. RING1 inhibits CD147’s capability promoting melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The human melanoma cell lines A375, SK-Mel-5, and SK-Mel-28 were purchased from the ATCC (Manassas, VA, USA), and the BRAFi-resistant cell line, called RA, was generated as described in a previous study [9,29]. JB6 mouse skin epidermal cell line, BJ human skin fibroblast cell line,PIG1 human melanocyte cell line, H9C2 human heart myoblast cell line were purchased from the ATCC.…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…The human melanoma cell lines A375, SK-Mel-5, and SK-Mel-28 were purchased from the ATCC (Manassas, VA, USA), and the BRAFi-resistant cell line, called RA, was generated as described in a previous study [9,29]. JB6 mouse skin epidermal cell line, BJ human skin fibroblast cell line,PIG1 human melanocyte cell line, H9C2 human heart myoblast cell line were purchased from the ATCC.…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…SKCM is the most malignant tumor among all skin tumors, owing to its highly invasive and metastatic potential[8], and the prognosis is extremely poor. Although SKCM only accounts for 4% of all skin cancers, it accounts for nearly 80% of all skin cancer-related deaths [9][10][11]. Early melanoma can be effectively treated by prompt surgical resection [12].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of the SCN8A gene (encoding type VIII alpha subunit of voltage gated sodium channel), which was down-regulated in the sensitive-and upregulated in the resistant spheroids, was described for several tumour types and it has been found that SCN8A gene expression level is significantly lower in tumour tissues compared to paired normal tissues [47]. Similarly, ring finger protein-1 (RING1) was also found as a differently expressed gene, which is involved in epigenetic regulation in cancer [48], where it acts as a transcriptional repressor and plays an important role in the development of aggressive phenotypes in melanoma [49]. Furthermore, upregulation of the ABHD4 gene was also common in resistant spheroids compared to sensitive ones.…”
Section: Discussionmentioning
confidence: 99%